2016
DOI: 10.1097/crd.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Aneurysms and Risk Factors for Adverse Events

Abstract: An abdominal aortic aneurysm (AAA) is a focal full thickness dilatation of the abdominal aorta, greater than 1.5 times its normal diameter. Although some patients with AAA experience back or abdominal pain, most remain asymptomatic until rupture. The prognosis after AAA rupture is poor. Management strategies for patients with asymptomatic AAAs include risk factor reduction, such as smoking cessation, optimizing antihypertensive treatment, and treating dyslipidemia, as well as surveillance by ultrasound. Curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…The specific mechanism initiating and leading to progression of AAA has not yet been elucidated; however, AAA development has been associated with a variety of infections like brucellosis, salmonellosis and tuberculosis, trauma and connective tissue disorders, Takayasu disease and Marfan syndrome. Identified risk factors for aneurysm development include older age, male gender, cigarette smoking, obesity, dysregulation of lipid levels, hypertension [ 2 , 10 , 11 , 12 ] and genetic predisposition [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The specific mechanism initiating and leading to progression of AAA has not yet been elucidated; however, AAA development has been associated with a variety of infections like brucellosis, salmonellosis and tuberculosis, trauma and connective tissue disorders, Takayasu disease and Marfan syndrome. Identified risk factors for aneurysm development include older age, male gender, cigarette smoking, obesity, dysregulation of lipid levels, hypertension [ 2 , 10 , 11 , 12 ] and genetic predisposition [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study demonstrated that circulating biomarkers of endothelial dysfunction in atherosclerosis patients (white blood cell count, fibrinogen, D-dimer, troponin T, N-terminal pro-brain natriuretic peptide, and high-sensitivity C-reactive protein) are also closely related to the occurrence and incidence of AAA [ 33 ]. Epidemiological surveys show that AAA risk factors, such as aging, smoking, male sex, high blood pressure, hyperlipidemia, atherosclerosis, and hyperhomocysteinemia, are the main factors that cause damage to endothelial cells leading to endothelial dysfunction [ 34 36 ]. For instance, the prevalence of AAA in the population who smoke is four times greater than those who do not smoke, meaning smoking is detrimental to endothelial function and thus closely related to many cardiovascular diseases [ 34 , 37 ].…”
Section: Clinical Evidence For Endothelium Involvement In Aaamentioning
confidence: 99%
“…Epidemiological surveys show that AAA risk factors, such as aging, smoking, male sex, high blood pressure, hyperlipidemia, atherosclerosis, and hyperhomocysteinemia, are the main factors that cause damage to endothelial cells leading to endothelial dysfunction [ 34 36 ]. For instance, the prevalence of AAA in the population who smoke is four times greater than those who do not smoke, meaning smoking is detrimental to endothelial function and thus closely related to many cardiovascular diseases [ 34 , 37 ]. Furthermore, recent studies in humans indicate that some endothelial protective medications such as statins, angiotensin-converting enzyme inhibitors (ACEIs), and AT 1 receptor blockers (ARBs) may be helpful to inhibit aneurysm rupture and growth, yet the effect is unclear in some larger cohort reports [ 38 , 39 ].…”
Section: Clinical Evidence For Endothelium Involvement In Aaamentioning
confidence: 99%
“…Abdominal aortic aneurysm (AAA) is a cardiovascular disease characterized by aortic dilation that exceeds the normal diameter by 50% or exceeds 3 cm in the infra-renal region 1 . Age, male gender, family history of AAA, smoking and hypertension are all risk factors related to AAA 2 . According to the population-based ultrasound screening studies, the prevalence of AAA is 4–7% in male and 1–2% in female over the age of 65 3 .…”
Section: Introductionmentioning
confidence: 99%